Marsupialisation of 12 odontogenic cysts in Boxer dogs: Retrospective case series - Haseler, James; Tundo, Ingrid; Southerden, Pete (Frontiers in Veterinary Science, 2023)
Marsupialisation of odontogenic cysts is a minimally invasive treatment method used in human dentistry. Marsupialisation decompresses the cyst and promotes remodelling of alveolar bone and shrinkage of the cyst. In this retrospective study we look at the effectiveness of marsupialisation at reducing the size of odontogenic cysts in dogs. The case series consists of 6 boxer dogs with 12 odontogenic cysts. Each case underwent a high-resolution CT scan prior to treatment and at follow-up. Each CT scan was reviewed, the volume of each cyst calculated using manual segmentation and the reduction in cyst volume calculated. There was a significant reduction in cystic volume of 66.6% over a mean of 138 days. This shows that the use of marsupialisation effective method of reducing cyst volume.